Crystal structure of the Cenp-HIKHead-TW sub-module of the inner kinetochore CCAN complex. Issue 19 (25th September 2020) - Zhang, Ziguo; Bellini, Dom; Barford, David
Abstract: Kinetochores are large multi-subunit complexes that attach centromeric chromatin to microtubules of the mitotic spindle, enabling sister chromatid segregation in mitosis. The inner kinetochore constitutive centromere associated network (CCAN) complex assembles onto the centromere-specific Cenp-A nucleosome (Cenp-A Nuc ), thereby coupling the centromere to the microtubule-binding outer kinetochore. CCAN is a conserved 14–16 subunit complex composed of discrete modules. Here, we determined the crystal structure of the Saccharomyces cerevisiae Cenp-HIK Head -TW sub-module, revealing how Cenp-HIK and Cenp-TW interact at the conserved Cenp-HIK Head –Cenp-TW interface. A major interface is formed by the C-terminal anti-parallel α-helices of the histone fold extension (HFE) of the Cenp-T histone fold domain (HFD) combining with α-helix H3 of Cenp-K to create a compact three α-helical bundle. We fitted the Cenp-HIK Head -TW sub-module to the previously determined cryo-EM map of the S. cerevisiae CCAN–Cenp-A Nuc complex. This showed that the HEAT repeat domain of Cenp-I Head and C-terminal HFD of Cenp-T of the Cenp-HIK Head -TW sub-module interact with the nucleosome DNA gyre at a site close to the Cenp-A Nuc dyad axis. Our structure provides a framework for understanding how Cenp-T links centromeric Cenp-A Nuc to the outer kinetochore through its HFD and N-terminal Ndc80-binding motif, respectively.